Syarifah Salwa Al-Attas dan Majelis Nururrahmah: Menguatkan Muslimah di Medan - Harahap, Artika Hazra; Andina, Syahna Wulan; Awiyah, Dumel; Siregar, Yusra Dewi (Islam & Contemporary Issues, 2024)
This study aims to examine the role of Syarifah Salwa Al-Attas and the Nururrahmah Assembly in strengthening the position and role of Muslim women in Medan. Syarifah Salwa Al-Attas is an influential Muslim female figure in her community, while the Nururrahmah Assembly is an organization focused on empowering women through religious education, skill development, and quality of life improvement. Using a qualitative approach with a case study method, this research collects data through in-depth interviews, participatory observation, and document analysis. The results show that Syarifah Salwa Al-Attas has successfully inspired many Muslim women in Medan to be more active in social and religious life. The Nururrahmah Assembly has provided various programs that not only enhance religious understanding but also strengthen the economic and social capacities of its members. The study concludes that the combination of inspirational leadership and comprehensive empowerment programs is highly effective in strengthening Muslim women in Medan, making them more independent and competitive in various aspects of life.